ASSESSMENT OF EFFECTIVENESS OF CITIZEN REGISTRATION SYSTEMS IN KENYA. - KIMOTHO, REUBEN M.; OLUOCH, DR. KEN (Journal of Public Policy and Administration, 2016)
Purpose: The study is an assessment of effectiveness of citizen registration systems in Kenya. Methodology: The study adopted a descriptive research design. The target populations were the Registration officials of the Department of National Registration Bureau and identity card applicants. A total sample size of 384 respondents (284 applicants and 100 officers) was taken from the provinces of Nairobi, Northern Eastern, Central and Coast Regions. Two sets of questionnaires were used for data collection. Descriptive statistics was used to present the findings Results: The findings from this study indicate that critical several institutional and capacity related factors exist that adversely affect registration of the Kenyan citizen Unique contribution to theory, practice and policy: The significant recommendation by the study is formulation of a single policy and legal framework to cater for registration of births and identity cards processing under a single Semi-Autonomous Government Agency. This should be complemented with setting up a single comprehensive database and national register